Reduction of fusarium wilt of "banana-maçã" by inoculation of arbuscular mycorrhizal fungi - Borges, Andréa Jaqueira da Silva; Trindade, Aldo Vilar; Matos, Aristóteles Pires de; Peixoto, Maria de Fátima da Silva (Pesquisa Agropecuaria Brasileira, 2007)
This work aimed to evaluate inoculum density of arbuscular mycorrhizal fungi (AMF) on incidence and effects of Fusarium oxysporum f. sp. cubense (FOC) on Maçã variety of banana (Musa sp.) during its initial growth. An experiment was conducted at Embrapa Mandioca e Fruticultura Tropical, under greenhouse conditions, comprising three stages: a test to adjust levels of inoculum of AMF to be set on the experiment was carried out; therefore, plantlets of banana were inoculated with Gigaspora margarita and, after 60 days, they were inoculated with FOC. G. margarita was efficient for growth of banana plantlets; previous inoculation of AMF reduced disease index caused by FOC, depending on level of inoculum of AMF; previous inoculation of AMF on banana plantlets resulted in bioprotection to FOC, related to level of colonization and level of inoculum of FOC in soil.